2019
DOI: 10.1186/s12913-018-3808-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patient and family perceptions of team processes and outcomes in healthcare teams: questionnaire development and psychometric evaluation

Abstract: BackgroundThere is a lack of validated instruments examining dimensions of team functioning from the perspective of patients and families consistent with a conceptual framework. The study aimed to develop and assess the psychometric properties of the Patient-Perceptions of Team Effectiveness (PTE) questionnaire.MethodsA cross-sectional survey was undertaken in three studies. Data were collected from May–October 2016 for Study 1, April 2018-ongoing for Study 2, and October 2016 to June 2017 for Study 3. Online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 81 publications
0
25
0
2
Order By: Relevance
“…Taken together, all these elements call for considering SDM in mental health care as a continuous, multipersonal process, not completed within a limited time period or with a single decision. 18,19 Ozdemic and Finkelstein have suggested that the longtime nature of chronic conditions provides a knowledge ripeness of how the illness and its suffering is understood and that we should be aware of the changes in the patients' self when recovering and the complexity that develops regarding decisions made. 20 As many of the mental illnesses are long-term conditions, we suggest this is relevant for how practitioners in mental health care understand the patient views.…”
Section: The Complexity Of Sdm In Mental Health Carementioning
confidence: 99%
“…Taken together, all these elements call for considering SDM in mental health care as a continuous, multipersonal process, not completed within a limited time period or with a single decision. 18,19 Ozdemic and Finkelstein have suggested that the longtime nature of chronic conditions provides a knowledge ripeness of how the illness and its suffering is understood and that we should be aware of the changes in the patients' self when recovering and the complexity that develops regarding decisions made. 20 As many of the mental illnesses are long-term conditions, we suggest this is relevant for how practitioners in mental health care understand the patient views.…”
Section: The Complexity Of Sdm In Mental Health Carementioning
confidence: 99%
“…Additionally, it is important to recognize that mental illnesses evolve through periods of recovery and relapse (Perestelo-Perez et al, 2011;Beitinger et al, 2014;Morant et al, 2016). All these elements call for considering SDM in mental health care a continuous process that involves multiple people, which cannot be restricted to a single decision or a particular consultation (Chong et al, 2013a;Kilpatrick et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Interprofessionality as a modifying mechanism of health care team practices involves effective communication actions, participation in decision making, cohesion, coordination of services and problem solving, and it is recognized that the lack of those factors diminishes the effectiveness of the results. In the United States, a review of 23.000 allegations of neglect highlighted poor communication as one of the main components responsible for the inadequate functioning of a health care team, resulting in a cost of US$ 1.7 billion and loss of about 2.000 lives (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a worldwide increasing need for the development of complex practices that are based on interdisciplinarity and interprofessionalism in order to achieve quality results in health care, through collaboration among professionals and expansion of interdisciplinary health care models (4)(5)(6) . Furthermore, there is an increasing perception that unidisciplinarity achieves ineffective results in front of the complexity of the health process and the illness of communities and population (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation